Wayside School gets a little stranger - Sachar, Louis, 1954-; Schick, Joel (London Bloomsbury Publishing Plc, 2010)
Unusual things continue to happen in the classroom on the thirtieth floor of Wayside School, which was accidentally built sideways with one classroom on each story.
Keywords: Humorous stories; Schools -- Juvenile fiction